Noncanonical MicroRNAs and Endogenous siRNAs in Lytic Infection of Murine Gammaherpesvirus - Xia, Jing; Zhang, Weixiong (PLOS ONE, 2012)
MicroRNA (miRNA) and endogenous small interfering RNA (endo-siRNA) are two essential classes of small noncoding RNAs (sncRNAs) in eukaryotes. The class of miRNA is diverse and there exist noncanonical miRNAs that bypass the canonical miRNA biogenesis pathway. In order to identify noncanonical miRNAs and endo-siRNAs responding to virus infection and study their potential function, we sequenced small-RNA species from cells lytically infected with murine gammaherpesvirus 68 (MHV68). In addition to three novel canonical miRNAs in mouse, two antisense miRNAs in virus and 25 novel noncanonical miRNAs, including miRNAs derived from transfer RNAs, small nucleolar RNAs and introns, in the host were identified. These noncanonical miRNAs exhibited features distinct from that of canonical miRNAs in lengths of hairpins, base pairings and first nucleotide preference. Many of the novel miRNAs are conserved in mammals. Besides several known murine endo-siRNAs detected by the sequencing profiling, a novel locus in the mouse genome was identified to produce endo-siRNAs. This novel endo-siRNA locus is comprised of two tandem inverted B4 short interspersed nuclear elements (SINEs). Unexpectedly, the SINE-derived endo-siRNAs were found in a variety of sequencing data and virus-infected cells. Moreover, a murine miRNA was up-regulated more than 35 fold in infected than in mock-treated cells. The putative targets of the viral and the up-regulated murine miRNAs were potentially involved in processes of gene transcription and protein phosphorylation, and localized to membranes, suggesting their potential role in manipulating the host basal immune system during lytic infection. Our results extended the number of noncanonical miRNAs in mammals and shed new light on their potential functions of lytic infection of MHV68.